The economics of immigration : theory and policy - Bodvarsson, Orn B. (Springer New York, 2013)
The Economics of Immigration is written as a both a reference for researchers and as a textbook on the economics of immigration. It is aimed at two audiences: (1) researchers who are interested in learning more about how economists approach the study of human migration flows; and (2) graduate students taking a course on migration or a labor economics course where immigration is one of the subfields studied. The book covers the economic theory of immigration, which explains why people move across borders and details the consequences of such movements for the source and destination economies. The book also describes immigration policy, providing both a history of immigration policy in a variety of countries and using the economic theory of immigration to explain the determinants and consequences of the policies. This second edition reflects the growing importance of immigration as an economic, political, and social issue in the USA, the EU, Japan, and nearly all other developed and developing countries of the world.